Non-Associative and Non-Commutative Algebra and Operator Theory NANCAOT, Dakar, Senegal, May 23–25, 2014: Workshop in Honor of Professor Amin Kaidi /: NANCAOT, Dakar, Senegal, May 23–25, 2014: Workshop in Honor of Professor Amin Kaidi. (2016) - Unknown
No abstract available